Optimizing Digital Marketing Product Strategy for MSMEs At Tanwir Study Members in Malang - Saleh, Akhmad Muwafik; Hakim, Andy Ilman (Abdimas Indonesian Journal, 2025)
The promotion of a creative economy based on transformative communication is a strategic effort that integrates economic, social, and cultural aspects through transformative communication processes. This approach aims to do more than just increase creative economy income; It also creates a space for dialogue that enables sustainable social transformation. In this context, transformative communication plays a central role as a medium that drives paradigm change among society. Participatory and inclusive communication allows diverse groups—including those marginalized—to participate in discussions and decision-making about the direction of the creative economy. Through in-depth interactions, communities can realize the previously neglected potential of local economies and begin to develop creative ideas that are relevant to their social and cultural environment. The form of the result is a more transformative concept of creative economy development, fully involving the community in the process of economic advancement in question. This process focuses not only on the development of individual skills, but also on the creation of collaborative networks that strengthen the creative economy ecosystem. Collaboration between artists, entrepreneurs, communities, and governments sparked local innovations that were able to compete in a wider market, both nationally and globally. Transformative communication encourages people to view creativity no longer as a mere product, but as a tool for social change, economic empowerment, and the enforcement of cultural identity.